Penerapan Korsase Bunga Mawar Putih pada Busana Pengantin Modern - Alya Musanny Nst; Nofi Rahmanita; Mega Kencana; Novina Yeni Fatrina (INDO PUBLISHING, 2026)
The creation of this work was motivated by the artist's interest in white roses which were then realized through corsages. Corsage is a decorative technique in the form of a flower arrangement or decorative ornament used to beautify clothing. White roses were chosen because they have the meaning of purity, holiness. In addition, the development of modern bridal fashion that is increasingly flexible and follows today's needs has become an inspiration in creating elegant, feminine, and timeless designs. The purpose of creating this work is to realize a modern bridal fashion design with the application of a white rose corsage as the main concept. The creation method is carried out through the stages of idea exploration, design design, material selection, and the clothing production process with standard boutique sewing techniques. The work is realized in three levels of clothing, namely ready to wear, ready to wear deluxe, and haute couture. The clothing uses bridal satin material combined with Tille candy sugar, organza, and Palembang songket. The results of the creation of this work show that the application of a white rose corsage can provide an elegant, luxurious, and romantic aesthetic value to modern bridal clothing. Each design has distinct characteristics depending on the level of the garment, ranging from slim dress silhouettes with simple details in ready-to-wear, to more structured details in deluxe ready-to-wear, to the majestic ballgown shapes in haute couture. This work is expected to inspire the development of modern bridal wear designs with decorative touches of white rose corsages.